Epidemiological analysis of craniofacial lesions and correlation between initial clinical and histopathological diagnoses at a craniofacial diagnostic center (Research, Society and Development, 2025)
Objective: This study aims to examine the prevalence and distribution of craniofacial lesions and to evaluate the correlation between preliminary clinical diagnoses and histopathological diagnoses. Methodology: This research was conducted at a center specialized in maxillofacial diseases, located in a city within the metropolitan region of São Paulo, during the period from 2018 to 2024. Direct source documentary research in a descriptive, retrospective, and cross-sectional study was carried out. Results: This study analyzed the prevalence and distribution of cranio-maxillofacial lesions in 1,620 patients treated at a specialized center in São Paulo. Conclusions: Most cases showed a significant correlation of 63.4% between preliminary clinical diagnoses and histopathological results. The findings highlight the importance of complementary examinations, such as biopsies, for accurate diagnosis and appropriate management of oral lesions.